Organizational Communication Strategies in Building Loyalty of Educators and Educational Staff at Pesantren Ar-Raudlatul Hasanah Medan - Carles Ginting; Humaizi; Dewi Kurniawati (Indonesian Journal of Advanced Research, 2024)
The research aims to analyze organizational communication, communication climate, and conflict resolution in building the loyalty of educators and educational staff at Pesantren Ar-Raudlatul Hasanah, Medan, North Sumatra. This research uses a constructivist paradigm with a descriptive qualitative approach. Data collection techniques were carried out using interviews of informants from the Director, Manager of Finance, Secretary, and four senior teachers, participant observation, and document analysis. The results of the research show that the organizational communication strategy at Pesantren Ar-Raudlatul Hasanah is to build the loyalty of educators and education staff through establishing a good communication climate with a human relations approach. A healthy communication climate is formed by a democratic leadership style, so that policies and rules implemented based on mutual agreement can be well accepted by subordinates. Resolving conflicts in organizations through a compromise strategy approach that does not harm either party.